HEAT AND MASS TRANSFER DURING FILTRATION DRYING - Utkirbek Khamdamov; Gulnorakhan Khasanova (Western European Studies, 2024)
The article analyzes the process of heat and mass transfer during filtration drying through a layer of dried material. Equations are presented to describe the transfer of heat from a gas flow to particles of wet material, experimental data according to the values of the Nusselt and Sherwood criteria. A leveling is given to determine the mass transfer coefficient with a known heat transfer coefficient
Keywords: filtration drying; heat transfer coefficient; mass transfer